2005
DOI: 10.1021/ma047850+
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Linking of Brominated Poly(isobutylene-co-isoprene) by N-Alkylation of the Amidine Bases DBU and DBN

Abstract: An unusual cross-linking of brominated poly(isobutylene-co-isoprene), BIIR, has been shown to occur in the presence of the normally nonnucleophilic amidine bases 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) and 1,5-diazabicyclo[4.3.0]non-5-ene (DBN). Model compound studies using brominated 2,2,4,8,8-pentamethyl-4-nonene (BPMN) have provided structural information which indicates that this cross-linking most likely occurs through a sequence of reactions which involves the following:  (1) N-alkylation of the amidine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…The peaks at 164.3 and 114.4 ppm can therefore be assigned to the ipso carbon and ortho carbon of the p -nitrophenyl substituent in 14c . This observation was particularly interesting as N-alkylation of DBN [36] was not favored and instead underwent substitution. To test if the reaction favors both – nucleophilic addition as well as substitution – at lower temperature, the reaction was performed at room temperature for 1.5 h. Although both products were observed the substitution product was minor product, as seen by the integration of p -nitrophenol peaks in the 1 H NMR.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks at 164.3 and 114.4 ppm can therefore be assigned to the ipso carbon and ortho carbon of the p -nitrophenyl substituent in 14c . This observation was particularly interesting as N-alkylation of DBN [36] was not favored and instead underwent substitution. To test if the reaction favors both – nucleophilic addition as well as substitution – at lower temperature, the reaction was performed at room temperature for 1.5 h. Although both products were observed the substitution product was minor product, as seen by the integration of p -nitrophenol peaks in the 1 H NMR.…”
Section: Resultsmentioning
confidence: 99%
“…While DBN was reportedly selected as an additive in preference to triethylamine due to its non-nucleophilic nature, ,, lactam products arising from nucleophilic attack of DBN and subsequent ring scission have been reported. In the case at hand, the configuration of the oxazole α-carbon has an influence on the reaction outcome: whereas the S * relative configuration in 69b allows for complete dehydration to 70 (and hence formation 59 ), the formation of oxidized product 60 suggests that the corresponding dehydration of R *-configured alcohol 69a is less facile…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic amidine bases such as DBU also support rapid and efficient BIIR cures. Previous model compound and rheological studies have shown that DBU is stable to hydrolysis, but highly susceptible to N ‐alkylation by allylic bromide (Scheme ) [8]. The resulting amidinium ion hydrolyzes readily to give an aminolactam intermediate [18], which displaces bromide from BIIR to give a thermoset product.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamics of simple bromide displacements follow bimolecular substitution kinetics, whereas a latent nucleophile can provide additional degrees of freedom to those interested in exploiting N ‐alkylation chemistry. Latent nucleophiles that are thermally activated may support vulcanization processes that do not suffer from scorch safety issues, while latent forms that are hydrolytically sensitive, such as bicyclic amidines [8], may support products intended for moisture‐curing applications.…”
Section: Introductionmentioning
confidence: 99%